2015
DOI: 10.1007/s11999-014-3772-x
|View full text |Cite
|
Sign up to set email alerts
|

Do Various Factors Affect the Frequency of Manipulation Under Anesthesia After Primary Total Knee Arthroplasty?

Abstract: Background One of the most important goals of primary total knee arthroplasty (TKA) is to achieve a functional range of motion (ROM). However, up to 20% of patients fail to do so, which can impair activities of daily living. Questions/purposes The purpose of this study was to evaluate the effect of various (1) demographic factors;(2) comorbidities; and (3) knee-specific factors on the frequency of manipulation under anesthesia, which was used as an indicator of knee stiffness after a primary TKA. Methods We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 18 publications
2
45
0
Order By: Relevance
“…This study found that patients who undergo manipulation after primary TKA have a significantly higher risk of revision, lower survivorship, as well as worse long-term ROM and 5,[10][11][12][13][14][15]27 Of all these factors, preoperative ROM is the best predictor of postoperative ROM. [10][11][12]27 Patients in this study who required a manipulation were significantly younger, had less preoperative knee ROM, and higher incidence of posttraumatic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that patients who undergo manipulation after primary TKA have a significantly higher risk of revision, lower survivorship, as well as worse long-term ROM and 5,[10][11][12][13][14][15]27 Of all these factors, preoperative ROM is the best predictor of postoperative ROM. [10][11][12]27 Patients in this study who required a manipulation were significantly younger, had less preoperative knee ROM, and higher incidence of posttraumatic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent knee stiffness occurs in 1.3 to 5.3% of patients undergoing TKA, which may result in a decreased range of motion (ROM) and impede activities of daily living. [3][4][5][6][7] While no validated criteria or consensus defining postoperative subjective knee stiffness exists, studies have defined it as a flexion contracture between 15 to 90 degrees. 3,5 Several intraoperative risk factors that contribute to knee stiffness after TKA have been identified, including improper flexionextension gap balancing, component malpositioning, inadequate femoral or tibial resection, excessive joint line elevation, creation of an anterior tibial slope, and incomplete resection of posterior osteophytes.…”
mentioning
confidence: 99%
“…6,7 A previous study by Issa et al, reviewing 3,182 TKAs of which 156 knees subsequently underwent MUA, found nonwhite race (odds ratio [OR]: 2.01), age less than 65, diabetes (OR: 1.72), high cholesterol (OR 2.70), tobacco smoking (OR: 1.59), knee osteonecrosis (OR: 3.61), and pre-TKA ROM less than 100 degrees (OR: 0.80) to be correlated to an increased risk of MUA. No difference was observed when comparing cruciate-retaining versus posterior-stabilized TKAs liner…”
mentioning
confidence: 99%
“…Knee stiffness following TKA is a potentially debilitating complication that can affect up to 20% of patients. [1][2][3] This complications may impair the patient's ability to perform frequent activities of daily living such as rising from the seated position, ascending and descending stairwells, as well as many others. 4 Additionally, range of motion (ROM) is one of the most important factors for quality of life and satisfaction in post TKA patients.…”
mentioning
confidence: 99%